The late 19th century archive in contemporary Latin American literature (Anclajes, 2021)
Late 20th and early 21st century Latin American literature rereads and problematizes late 19th-century Latin American Modernism. This article examines some of these genealogies in order to analyze the significance of this literary dialogue in our present time.
Keywords: Latin American literature; archive; Modernism; end of the century; XXI century